Assessing the Composition of 19th Century Lime Mortars from a Mission Chapel in the Former Hacienda de San Isidro de Mariquina Philippines - Jan-Michael Cayme; Renz Matthew L. L. Aurellano; Carmen Luisa P. Cabral; Gellyn Ann R. Alonzo; Aniano N. , Jr. Asor (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2018)
This paper presents the results of a chemical study on lime mortars manufactured during the Spanish Colonial Period in the Philippines. Lime mortar samples, MRK-01 and MRK-02, were obtained from the facade of a historical mission chapel in Marikina City. The nature of the aggregate and binder components in these mortar samples were determined by performing sieve analysis and classified to be poorly graded with uniform gradation. An aggregate to binder ratio of approximately 1:1 was computed based on the solubility of the individual sieved fractions in hydrochloric acid. The silicate character of the aggregate was confirmed by the absorbance peaks attributed to silicon dioxide (SiO2) in the Fourier Transform Infrared Spectroscopy (FTIR). Natural river sand was used as aggregates in both mortar samples which is apparent from the particle shapes of the sieved fractions. There was also no evidence of sea shells, broken potteries, brick fragments and bulk unburned limestone used as aggregates in any of the mortar samples tested. The binder portion is mainly calcitic or calcium carbonate (CaCO3) based on the FTIR spectra and was shown to be removed by hydrochloric acid digestion. Titration method using ethylenediaminetetraacetic acid (EDTA) was employed to determine the amount of calcium in the acid soluble fractions. The percentage of calcium for MRK-01 ranges from about 1.0% to 9.5%, while MRK-02 ranges from about 2.3% to 16.8%, respectively. These percentages indicate that MRK-02 was manufactured with more lime binder compared to MRK-01. From this study, a simple method of understanding the composition of old lime mortars in the Philippines was established, which is useful for general heritage conservation work.